(untitled) (International journal of artificial intelligence, 2024)
one of the methods in which the teacher's, pedagogical skills significantly affect the increase in his qualifications, pedagogical abilities, pedagogical competence is the improvement of the qualifications of Continuing Professional Education. This article will talk about professional competencies in future specialists, methodological competence, its components, the tasks of methodological competence and how to formulate this competence in primary school teachers.